Nickel slag-acetylene residue composite mineral admixture based on industrial flue gas carbonization and preparation method of nickel slag-acetylene residue composite mineral admixture

Through the industrial flue gas nickel carbide slag-acetylene residue composite mineral blend, the concrete volume instability caused by calcium oxide, calcium hydroxide and magnesium oxide in acetylene residue and nickel residue is solved, and the mechanical properties and durability of concrete are improved. and realize solid waste resource utilization and low carbon emissions.

CN119219357APending Publication Date: 2024-12-31JIANGSU ZHONGDING BUILDING MATERIALS GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411131202.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-17
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The high content of calcium oxide, calcium hydroxide and magnesium oxide in acetylene residue and nickel slag leads to the instability of concrete products.

Method used

Using industrial flue gas nickel carbide slag-acetylene residue composite mineral blend, the content of calcium oxide and calcium hydroxide is reduced through ball milling and suspension formation technology, and the dense porous structure and strong adsorption carbonization products are generated, which enhances the adhesion and Reduce volume instability.

Benefits of technology

It improves the mechanical properties and durability of concrete, meets the performance requirements of ordinary grade II blends, and realizes solid waste resource utilization and low carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a nickel slag-acetylene residue composite mineral admixture based on industrial flue gas carbonization and a preparation method of the nickel slag-acetylene residue composite mineral admixture. The nickel slag-acetylene residue composite mineral admixture comprises acetylene residue powder, nickel slag powder, sodium tripolyphosphate, sodium polyacrylate, an exciting agent and water. The preparation method comprises the following steps: stirring acetylene residue powder, nickel slag powder and water to form a mixed slurry, adding sodium tripolyphosphate and sodium polyacrylate, stirring to form a stable turbid liquid, adding an exciting agent into the turbid liquid, uniformly stirring to prepare a mixture, and finally carbonizing the mixture for 4 hours by adopting industrial flue gas under the conditions that the temperature is 75 DEG C and the pressure is 1.5-2.0 MPa. The composite mineral admixture is prepared. The carbonized nickel slag-acetylene residue composite mineral admixture can equivalently replace 30% of cement to prepare mortar test blocks, the mortar fluidity ratio reaches 102% or above, the 7-day activity index reaches 72% or above, and the 28-day activity index reaches 79% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite mineral admixtures, and in particular relates to a nickel slag-acetylene residue composite mineral admixture based on industrial flue gas carbonization and a preparation method thereof. Background Art

[0002] Acetylene residue is the solid carbide slag obtained from carbide slurry wastewater produced in the process of producing acetylene gas. The CaO content of the solid carbide slag is as high as 60% or more after precipitation and drying. Studies have found that the chemical composition of acetylene residue is similar to that of slaked lime. It contains rich calcium sources and has a certain gelling property after grinding. It can replace part of cement to produce concrete products. However, the content of calcium oxide and calcium hydroxide in acetylene residue is relatively high. A large amount of Ca 2+ It exists in the form of free oxides. If hydration is incomplete, the presence of free calcium oxide in concrete products may easily cause problems such as volume stability.

[0003] In recent years, with the development of my country's nickel iron industry, the output and demand of nickel have continued to increase. Nickel slag is a solid waste discharged during the smelting of nickel iron alloy. Its main chemical components are SiO2, MgO, Fe2O3, and it always contains 0.1-3.5% Cr2O3.

[0004] Based on this, a mineral admixture is now studied, which can make full use of nickel slag and acetylene residue, improve the utilization of solid waste, and at the same time effectively solve the problem of volume stability in concrete products caused by high content of calcium oxide, calcium hydroxide and magnesium oxide in acetylene residue or nickel slag. Summary of the invention

[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a nickel slag-acetylene residue composite mineral admixture, which is fully carbonized based on industrial flue gas to effectively solve the problem of volume stability in concrete products caused by high contents of calcium oxide, calcium hydroxide and magnesium oxide in acetylene residue or nickel slag.

[0006] Technical solution: The present invention is based on a nickel slag-acetylene residue composite mineral admixture obtained by carbonization of industrial flue gas. The composite mineral admixture comprises the following raw materials by weight: 50-60 parts of acetylene residue powder, 5-10 parts of nickel slag powder, 1-1.5 parts of sodium tripolyphosphate, 1-1.5 parts of sodium polyacrylate, 0.5-1 parts of an activator and 15-40 parts of water.

[0007] The present invention is based on making full use of solid waste acetylene residue powder and nickel slag powder, adopts carbonization reaction to reduce the content of calcium oxide and calcium hydroxide in acetylene residue, and generates carbonized products with dense porous structure and strong adsorption, enhances the bonding of nickel slag and acetylene residue with aggregate in concrete, reduces the volume instability of acetylene residue, and thus improves the mechanical properties and durability of concrete. The method adopted is to compound sodium tripolyphosphate and sodium polyacrylate, combine with water to form a suspension, and the phosphate anions of sodium tripolyphosphate and the polyacrylate anions of sodium polyacrylate can be adsorbed on the surface of nickel slag and acetylene residue particles, making the surface of the particles more negatively charged, increasing the electrostatic repulsion, so that the nickel slag-acetylene residue suspension always maintains a suspended state during the carbonization process without sedimentation and coagulation, avoiding the deposition of acetylene residue and nickel slag during the carbonization process to cause solid-liquid stratification, thereby increasing the surface area of ​​nickel slag and acetylene residue particles to promote the sufficiency of the carbonization reaction; at the same time, sodium tripolyphosphate has a strong effect on the surface of nickel slag and acetylene residue particles. Alkali metal ions such as calcium and magnesium have strong complexing ability. In this system, they can also complex with metal ions in acetylene residue powder, nickel slag powder and mineral activator to form alkali metal complexes that are easily soluble in water, thereby increasing the solubility concentration of metal ions to promote the continuous precipitation of alkali metal ions such as calcium and magnesium in acetylene residue powder and nickel slag powder in the suspension system. In addition, sodium tripolyphosphate and sodium polyacrylate have strong suspension and dispersibility, which can effectively improve the suspension stability of alkali metal complexes in the suspension system, providing favorable reaction conditions for the forward progress of the carbonization reaction, thereby further promoting the sufficiency of the carbonization reaction.

[0008] Furthermore, the CaO content of the acetylene residue powder used in the admixture is ≥ 70%, and its specific surface area is ≥ 350m 2 / kg.

[0009] Furthermore, the nickel slag powder used in the admixture has A (CaO + MgO) ≥ 25% and a specific surface area ≥ 330m 2 / kg.

[0010] Furthermore, the activator used in the admixture is fly ash, light MgO or NaOH.

[0011] The present invention prepares the nickel slag-acetylene residue composite mineral admixture, comprising the following steps:

[0012] (1) Ball mill the acetylene residue powder and nickel slag powder separately to obtain a specific surface area ≥ 350m 2 / kg acetylene residue powder, specific surface area ≥330m 2 / kg nickel slag powder;

[0013] (2) stirring the ball-milled acetylene residue powder, nickel slag powder and water to form a mixed slurry;

[0014] (3) adding sodium tripolyphosphate and sodium polyacrylate and stirring to form a stable suspension, adding an activator to the suspension, stirring evenly to obtain a mixture;

[0015] (4) The mixture is carbonized using industrial flue gas at a temperature of 60-80° C. and a pressure of 1.5-2.0 MPa for 2-6 hours to obtain the composite mineral admixture.

[0016] Furthermore, in step (2) of preparing the admixture of the present invention, the stirring is performed by magnetic stirring at a stirring speed of 800-1000 r / min for 30 min.

[0017] Furthermore, in step (2) of preparing the admixture of the present invention, the CO2 concentration in the industrial flue gas is 20-35%.

[0018] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are: the admixture is based on the compound acetylene residue powder and nickel slag powder, and is carbonized by industrial flue gas. On the one hand, it makes full use of solid waste and industrial flue gas to achieve solid waste resource utilization and low-carbon emissions of steel plant flue gas; on the other hand, the carbonization method can effectively reduce the content of free oxides in acetylene residue and nickel slag, thereby reducing the impact of acetylene residue and nickel slag on the poor volume stability in the concrete system.

[0019] The present invention uses a carbonized nickel slag-acetylene residue composite mineral admixture to replace 30% of cement in an equal amount to prepare a mortar test block, and the mortar fluidity ratio reaches more than 102%, the 7-day activity index reaches more than 72%, and the 28-day activity index reaches more than 79%, meeting the performance requirements of ordinary type II grade admixtures in JG / T 486-2015 "Composite admixtures for concrete". DETAILED DESCRIPTION

[0021] The nickel slag-acetylene residue composite mineral admixture based on industrial flue gas carbonization comprises the following raw materials by weight: 50-60 parts of acetylene residue powder, 5-10 parts of nickel slag powder, 1-1.5 parts of sodium tripolyphosphate, 1-1.5 parts of sodium polyacrylate, 0.5-1 parts of activator and 15-40 parts of water.

[0022] The components of acetylene residue powder are shown in Table 1. The components of nickel slag powder are shown in Table 2. Sodium tripolyphosphate is a white crystalline powder, with a content of 56.0-60%, and a water-insoluble content of ≤0.03%. Sodium polyacrylate is a light yellow powder, with a content (in terms of Na2O) ≥24.5%.

[0023] The activator can be fly ash, light MgO or NaOH; the effective content of light MgO is ≥98.5%, chloride is ≤0.02%, and loss on ignition is ≤4.5%; the content of NaOH is ≥96%, and chloride is ≤0.005%.

[0024] The industrial flue gas used in the present invention is industrial waste gas from a steel plant after being treated with desulfurization, denitrification, dust removal and waste heat recovery, and its CO2 concentration is 20-35%.

[0025] Table 1 Component content of acetylene residue powder

[0026]

[0027] Table 2 Component content of nickel slag powder

[0028] Chemical composition CaO <![CDATA[SiO2]]> MgO <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> Other Elements content / % 8.4 29.8 22.3 11.7 19.6 margin

[0029] Example 1

[0030] The component contents of the nickel slag-acetylene residue composite mineral admixture of Example 1 are shown in Table 3 below.

[0031] Table 3 Component contents of the composite mineral admixture of Example 1

[0032] Serial number Components Weight parts / parts 1 Acetylene residue powder 50 2 Nickel slag powder 5 3 water 35 4 Sodium tripolyphosphate 1.2 5 Sodium polyacrylate 1.2 6 Fly ash 0.7

[0033] The preparation method of the composite mineral admixture of this embodiment 1 comprises the following steps:

[0034] (1) Ball mill the acetylene residue powder and nickel slag powder separately to obtain a specific surface area ≥ 350m 2 / kg acetylene residue powder, specific surface area ≥330m 2 / kg nickel slag powder;

[0035] (2) stirring the ball-milled acetylene residue powder, nickel slag powder and water to form a mixed slurry;

[0036] (3) adding sodium tripolyphosphate and sodium polyacrylate, and magnetically stirring at 950 r / min for 30 min to form a stable nickel slag-acetylene residue suspension, adding fly ash to the suspension, and stirring uniformly to obtain a mixture;

[0037] (4) carbonizing the mixture at a temperature of 75° C. and a pressure of 1.5 MPa using industrial flue gas with a CO2 concentration of 30% for 4 hours to obtain a carbonized material;

[0038] (5) The carbonized material is taken out, dried and ball-milled for 5 minutes to obtain the composite mineral admixture.

[0039] Example 2

[0040] The component contents of the nickel slag-acetylene residue composite mineral admixture of Example 2 are shown in Table 4 below.

[0041] Table 4 Component contents of the composite mineral admixture of Example 2

[0042]

[0043]

[0044] The preparation method of the composite mineral admixture of Example 2 is the same as that of Example 1.

[0045] Example 3

[0046] The component content and preparation method of the nickel slag-acetylene residue composite mineral admixture of Example 3 are basically the same as those of Example 1, except that the activator is light MgO.

[0047] Example 4

[0048] The component content and preparation method of the nickel slag-acetylene residue composite mineral admixture of Example 4 are basically the same as those of Example 2, except that the activator is light MgO.

[0049] Example 5

[0050] The component content and preparation method of the nickel slag-acetylene residue composite mineral admixture of Example 5 are basically the same as those of Example 1, except that the activator is NaOH.

[0051] Example 6

[0052] The component content and preparation method of the nickel slag-acetylene residue composite mineral admixture of Example 6 are basically the same as those of Example 2, except that the activator is NaOH.

[0053] Comparative Example 1

[0054] The basic steps are the same as those in Example 1, except that sodium tripolyphosphate and sodium polyacrylate are not added to the composite mineral admixture.

[0055] Comparative Example 2

[0056] The basic steps are the same as those of Example 2, except that sodium tripolyphosphate and sodium polyacrylate are not added to the composite mineral admixture.

[0057] Example 7

[0058] The component contents of the nickel slag-acetylene residue composite mineral admixture of Example 7 are shown in Table 5 below.

[0059] Table 5 Component contents of the composite mineral admixture of Example 7

[0060]

[0061]

[0062] The preparation method of the composite mineral admixture of Example 7 comprises the following steps:

[0063] (1) Ball mill the acetylene residue powder and nickel slag powder separately to obtain a specific surface area ≥ 350m 2 / kg acetylene residue powder, specific surface area ≥330m 2 / kg nickel slag powder;

[0064] (2) stirring the ball-milled acetylene residue powder, nickel slag powder and water to form a mixed slurry;

[0065] (3) adding sodium tripolyphosphate and sodium polyacrylate and magnetically stirring at 800 r / min for 30 min to form a stable nickel slag-acetylene residue suspension, adding fly ash to the suspension, stirring evenly, to obtain a mixture;

[0066] (4) carbonizing the mixture at a temperature of 75° C. and a pressure of 1.5 MPa for 4 hours using industrial flue gas with a CO2 concentration of 20% to obtain a carbonized material;

[0067] (5) The carbonized material is taken out, dried and ball-milled for 5 minutes to obtain the composite mineral admixture.

[0068] Example 8

[0069] The component contents of the nickel slag-acetylene residue composite mineral admixture of Example 8 are shown in Table 6 below.

[0070] Table 6 Component contents of the composite mineral admixture of Example 8

[0071] Serial number Components Weight parts / parts 1 Acetylene residue powder 60 2 Nickel slag powder 10 3 water 40 4 Sodium tripolyphosphate 1.5 5 Sodium polyacrylate 1.5 6 Fly ash 1

[0072] The preparation method of the composite mineral admixture of Example 8 comprises the following steps:

[0073] (1) Ball mill the acetylene residue powder and nickel slag powder separately to obtain a specific surface area ≥ 350m 2 / kg acetylene residue powder, specific surface area ≥330m 2 / kg nickel slag powder;

[0074] (2) stirring the ball-milled acetylene residue powder, nickel slag powder and water to form a mixed slurry;

[0075] (3) adding sodium tripolyphosphate and sodium polyacrylate and magnetically stirring at 1000 r / min for 30 min to form a stable nickel slag-acetylene residue suspension, adding fly ash to the suspension, stirring evenly, to obtain a mixture;

[0076] (4) carbonizing the mixture at a temperature of 75° C. and a pressure of 2.0 MPa using industrial flue gas with a CO2 concentration of 35% for 4 hours to obtain a carbonized material;

[0077] (5) The carbonized material is taken out, dried and ball-milled for 5 minutes to obtain the composite mineral admixture.

[0078] Performance Testing

[0079] Referring to the proportions in Table 7 below, the composite mineral admixtures prepared in Comparative Example 1, Comparative Example 2 and Examples 1-6 were used to prepare cement mortar according to GB / T 17671-2021 "Test Method for Cement Mortar Strength (ISO Method)" and the fluidity, 7-day and 28-day compressive strength of the mortar were measured. The fluidity ratio, 7-day activity index and 28-day activity index of the nickel carbide slag-acetylene residue composite mineral admixture were evaluated according to JG / T 486-2015 "Composite admixtures for concrete", and the results are shown in Table 8.

[0080] Table 7 Proportion of cement mortar (unit: gram)

[0081] cement Nickel carbide slag-acetylene residue admixture sand water 315±1 135±1 1350±5 225±1

[0082] Table 8 Performance of Comparative Example Mortar and Example Mortar

[0083]

[0084]

[0085] It can be seen from Table 8 that the mortar fluidity ratio of the composite mineral admixture prepared by the present invention reaches more than 102%, the 7-day activity index reaches more than 72%, and the 28-day activity index reaches more than 79%, which meets the performance requirements of ordinary type II admixtures in JG / T 486-2015 "Composite admixtures for concrete".

Claims

1. A nickel slag-acetylene residue composite mineral admixture based on industrial flue gas carbonization, characterized in that: The composite mineral admixture comprises the following raw materials by weight: 50-60 parts of acetylene residue powder, 5-10 parts of nickel slag powder, 1-1.5 parts of sodium tripolyphosphate, 1-1.5 parts of sodium polyacrylate, 0.5-1 parts of activator and 15-40 parts of water.

2. The nickel slag-acetylene residue composite mineral admixture based on industrial flue gas carbonization according to claim 1, characterized in that: The CaO content of the acetylene residue powder is ≥70%, and its specific surface area is ≥350m 2 / kg.

3. The nickel slag-acetylene residue composite mineral admixture based on industrial flue gas carbonization according to claim 1, characterized in that: The nickel slag powder has A (CaO + MgO) ≥ 25% and a specific surface area ≥ 330 m 2 / kg.

4. The nickel slag-acetylene residue composite mineral admixture based on industrial flue gas carbonization according to claim 1, characterized in that: The activator is fly ash, light MgO or NaOH.

5. A method for preparing the nickel slag-acetylene residue composite mineral admixture according to claim 1, characterized in that: The steps include: (1) Ball mill the acetylene residue powder and nickel slag powder separately to obtain a specific surface area ≥ 350m 2 / kg acetylene residue powder, specific surface area ≥330m 2 / kg nickel slag powder; (2) stirring the ball-milled acetylene residue powder, nickel slag powder and water to form a mixed slurry; (3) adding sodium tripolyphosphate and sodium polyacrylate and stirring to form a stable suspension, adding an activator to the suspension, stirring evenly to obtain a mixture; (4) The mixture is carbonized using industrial flue gas at a temperature of 60-80° C. and a pressure of 1.5-2.0 MPa for 2-6 hours to obtain the composite mineral admixture.

6. The method for preparing the nickel slag-acetylene residue composite mineral admixture according to claim 5, characterized in that: In step (2), the stirring is magnetic stirring at a stirring speed of 800-1000 r / min for 10-40 min.

7. The method for preparing the nickel slag-acetylene residue composite mineral admixture according to claim 5, characterized in that: In step (2), the CO2 concentration in the industrial flue gas is 20-35%.